Complete eradication of chronic lymphocytic leukemia with unusual skin involvement of high mitotic index after time‐limited venetoclax/obinutuzumab treatment. Issue 7 (23rd July 2021) - Dimou, Maria; Iliakis, Theodoros; Paradalis, Vasileios; Bitsani, Aikaterini; Kyrtsonis, Marie‐Christine; Panayiotidis, Panayiotis
Abstract: The novel time‐limited combinations with the bcl‐2 inhibitor venetoclax can induce deep responses even in CLL cases with unusual and biologically aggressive presentations, like the skin masses of our patient. Abstract : The novel time‐limited combinations with the bcl‐2 inhibitor venetoclax can induce deep responses even in CLL cases with unusual and biologically aggressive presentations, like the skin masses of our patient.